Triphasic Oxygen Storage in Wet Nanoparticulate Polymer of Intrinsic Microporosity (PIM-1) on Platinum: An Electrochemical Investigation - Azevedo Beluomini, Maisa [UNESP]; Ramos Stradiotto, Nelson [UNESP]; Boldrin Zanoni, Maria Valnice [UNESP]; Carta, Mariolino; McKeown, Neil B.; Fletcher, Philip J.; Sain, Sunanda; Li, Zhongkai; Marken, Frank (American Chemical Society (ACS), 2024)
The triphasic interaction of gases with electrode surfaces immersed in aqueous electrolyte is crucial in electrochemical technologies (fuel cells, batteries, sensors). Some microporous materials modify this interaction locally via triphasic storage capacity for gases in aqueous environments linked to changes in apparent oxygen concentration and diffusivity (as well as activity and reactivity). Here, a nanoparticulate polymer of intrinsic microporosity (PIM-1) in aqueous electrolyte is shown to store oxygen gas and thereby enhance electrochemical signals for oxygen reduction in aqueous media. Oxygen reduction current transient data at platinum disk electrodes suggest that the reactivity of ambient oxygen in aqueous electrolyte (typically Doxygen = 2.8 × 10-9 m2 s-1; coxygen = 0.3 mM) is substantially modified (to approximately Dapp,oxygen = 1.6 (±0.3) × 10-12 m2 s-1; capp,oxygen = 50 (±5) mM) with important implications for triphasic electrode processes. The considerable apparent concentration of oxygen even for ambient oxygen levels is important. Potential applications in oxygen sensing, oxygen storage, oxygen catalysis, or applications associated with other types of gases are discussed.
Keywords: diffusion layer; electrocatalysis; energy storage; oxygen evolution; triphasic gas storage